Regulation of adaptive immune responses by guiding cell movements in the spleen - Zhao, Lintao; Liu, Lina; Guo, Bo; Zhu, Bo (Frontiers in Microbiology, 2015)
The spleen combines the innate and adaptive immune systems in a uniquely organized way. The excision of spleen will induce many complications, especially the increased susceptibility to infections. Recent research shows that besides playing roles during the immune responses, the spleen is also an important organ during immunoregulation, which is different from other secondary lymphoid organs. This unique function is mainly realized by modulating cell migration and proliferation in the spleen. This review provides a better understanding of the functions of this complex organ gained from recent studies.